Berpikir Tentang Garis, Mengolah Garis Jadi Seni - Yulriawan Dafri (Ars: Jurnal Seni Rupa dan Desain, 2011)
Line is a crucial part of human life that is inseparable from the society. The significance of line can be viewed from various angles. It can be scrutinized based on its form and the point of view used in the analysis. In real life, line can be classified into two big classes: those that are natural- they exist naturally and those that are resulted from creative thinking process of human. Line is a vehicle by which an artist expresses himself and actualizing his ideas to be understood and appreciated as a work of art.Keywords: line, creating line, expression, art